Hazard and dangerous factors in nurses and midwifes work - Kowalczuk, Krystyna; Krajewska-Kułak, Elżbieta; Ostapowicz-Vandame, Katarzyna; Kułak, Wojciech (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Nurses and midwifes in their work are subjected to many hazard, dangerous and psychosocial factors. They are also subjected to many occupational hazards. This situation deteriorates an unsatisfactory system of the medico-prophylactic recommendations as result of poor knowledge on incidence of hazard factors and its types in the environment. In this article we analysed more common occupational hazards in nurses and midwifes work. Nursing Topics 2010; 18 (3): 353-357